Perilaku Konsumtif pada Penggemar K-Boygroup Seventeen (Carat) di Surabaya - Tasya Aulia Fatimah (Syntax Corporation Indonesia, 2024)
This research aims to, first: provide an overview of how excessive attitudes in consuming and buying something related to Seventeen are done by Carat in fully supporting his idols. Second: knowing the causes and how interested the Carat Surabaya community is in buying goods related to Carat. The method used in this study is descriptive qualitative with purposive sampling data collection. Data obtained through in-depth interviews, observation and documentation. The theory used in analyzing the data obtained is to use Jean Baudillard's theory of consumption society. The results of the study show that: (1) Carat has always had many ways to support her idols. By buying albums, it is seen as a form of loyalty and a way for them to appreciate their idols as art workers. (2) By purchasing merchandise related to Seventeen, it is their desire and desire as a fan to show that the items they buy are symbols and part of the fandom.